Experimental Evaluation and Analysis of LED Illumination Source for Endoscopy Imaging - Patel, Amit; Mewada, Hiren; Chaudhari, Jitendra; Mahant, Keyur; Vala, Alpesh (International Journal of Integrated Engineering, 2022)
The minimally invasive surgery uses a small instrument with camera and light to fit the tiny cut in the skin. The selection of the light depends on the power and driving current of the circuit. It can also help in the standardization of the camera and capture the tissues' true-colour image. This paper presents the LED source analysis used in the clinical endoscopes for surgery and the human body's medical examination. Initially, a LED source selection mechanism generating intense illuminance in a visible band is proposed. A low-cost prototype model is developed to analyze the wavelength and illuminance of three different LEDs types. An effect on variation in LED illumination is investigated by changing the distance between the Borescope and LED source. True-colour image generation and tissue contrast are more important in medical diagnostics. Therefore, a sigmoid function improving the whole contrast ratio of the captured image in real-time is presented. The results of spectrum and wavelength for a current variation are presented. Type 3 LED produces higher illumination (i.e., 395 Klux) and peak wavelength (i.e., 622.05 nm) than other LEDs, while type-2 LED has better FWHM for the blue colour spectrum. The modification in the sigmoid function enhances the image with 34.25 peak PSNR producing a true-colour image.